Physico-Chemical Analysis of Industrial Effluents Obtained from Taloja Industrial Estate (Maharashtra) - Lokhande, R.S.; Pimple, Deepali (Asian Journal of Chemistry, 2010)
The physico-chemical analysis of the industiral effluencts collected from Taloja MIDC (Maharashtta) has been analysed. It is observed that the industrial effluent contains high concentration of the metal ions, quite higher than the permissible limits indicating high degree of pollution in that industrial zone.